The Bose brothers and Indian independence : an insider's account - Bose, Madhuri (SAGE, 2016)
This book chronicles the roles of Sarat and Subhas Chandra Bose in the Indian freedom struggle. It draws  from first-hand accounts of Amiya Nath Bose who was close to them as family, political ally and also was a confidant and trusted envoy. The book takes us through the turbulent political arena of India in the 1920s and unravels the politics of the Indian Nationalist Movement as experienced by Sarat and Subhash Chandra Bose. It reveals their interactions with contemporary leaders Chittaranjan Das, Jinnah, Motilal and Jawaharlal Nehru, Vallabhbhai Patel and Mahatma Gandhi-down the years till Partition in 1947, an event which Sarat Bose relentlessly opposed. With access to diaries, notes, photographs and private correspondence, this book, written by a member of the Bose family, brings to light previously unpublished material on Netaji and Sarat Chandra Bose.